Backing the Blue: Trauma in Law Enforcement Spouses and Couples. Issue 2 (21st October 2019) - Landers, Ashley L.; Dimitropoulos, Gina; Mendenhall, Tai J.; Kennedy, Alison; Zemanek, Lindsey
Abstract : Objective: To explore the lived experiences of secondary trauma among partners of law enforcement professionals (LEPs). Background: Stress is a common occurrence for LEPs. Although research suggests that LEPs are directly affected by trauma exposure, few studies focus on the secondary trauma of partners or spouses of LEPs. Method: Utilizing transcendental phenomenological inquiry, in‐depth qualitative interviews were conducted with a purposeful sample of eight spouses of law enforcement recruited from community groups and police departments. Results: The results revealed three overarching themes of how participants experienced being partnered with an LEP: (a) types of trauma exposure, (b) the ripple impact of trauma, and (c) strength of couples and how they cope with trauma. Conclusion: Findings suggest that spouses are both affected by trauma and serve a supportive role to LEPs following trauma exposure. Because secondary trauma can exacerbate existing difficulties in communication and emotional intimacy within couples' relationships, a greater understanding of the impact of trauma on law enforcement couples may lead to greater resources to help support couples wherein one individual is directly exposed to work‐related trauma. Implications: Family professionals should promote healthy responses and coping among law enforcement couples following exposure to traumatic events.